Preliminary clinical assessment and non- toxicity evaluation of an ayurvedic formulation BGR-34 in NIDDM - B.P. Gupta (Journal of Traditional and Complementary Medicine, 2018)
In view of the overall health impact of NIDDM, inventers understand the necessity of improving glycemic control in adults with type 2 diabetes. BGR-34 provides an effective treatment option for adults with type 2 diabetes who have been inadequately controlled on lifestyle with or without other oral hypoglycemic agents (OHGAs) such as metformin, sulfonylurea, or a glitazones. BGR-34 is an appropriate option to consider for addition to a managed care drug formulary. Treatment with BGR-34 produced clinically relevant and statistically significant reductions in all three key measures of glucose control studied —FPG, PPBG and HbA1c— when compared with placebo. BGR-34, showed the promising result with respect to glycemic parameters in NIDDM patient with a significant reduction in fasting blood sugar by 34.3%, postprandial blood sugar 35.5% & glycosylated haemoglobin by 20.31% as compared to placebo group showing a reduction by 13.2%, 10.9% & 10.87% respectively. The trial has also been registered to CTRI, India. This study has been registered in the clinical trial registry-India. Keywords: BGR-34, Berberis aristata, NIDDM, Indian system medicine, Type 2 diabetes